Effects of peripheral electromagnetic stimulation after an eccentric exercise-induced delayed-onset muscle soreness protocol in professional soccer players: a randomized controlled trial - Keriven, Hugo; Sánchez-Sierra, Alberto; Miñambres-Martín, Diego; González de la Flor, Ángel; García-Pérez-de-Sevilla, Guillermo; Domínguez-Balmaseda, Diego (Frontiers in Physiology, 2023)
Objective: To examine the effects of peripheral electromagnetic stimulation in male professional soccer players on markers of Delayed Onset Muscular Soreness (DOMS), induced by a protocol of exercise (60 minutes of eccentric and plyometric) . Methods: A randomized controlled trial with fourty-five professional soccer players aged 22.33 ± 4.82 years participated in the study. Twenty-three participants were assigned to the experimental group with peripheral electromagnetic stimulation (5 stimulations of 5 seconds at 100 HZ with 55 seconds of rest for a total of 5 minutes of treatment) and the remaining 22 participants were assigned to the control group. Pain pressure threshold (PPT) of the vastus medialis, the Visual Analogue Scale-Fatigue (VAS-F), half squat (HS) test and the maximum voluntary contraction of the quadriceps were assessed. All evaluations were performed before and after 1h of the eccentric exercise induced DOMS, as well as at post 24-48, and 72 hours. Results: Group-by-time interaction was observed in PPT of the vastus medialis (p = 0.040) with a medium effect size (η2p = 0.069). From 48 to 72h the experimental group showed an increase of PPT compared to control group (p = 0.015). There was no group-by-time interaction for HS, quadriceps strength and VAS-F (p > 0.05). Conclusions: Peripheral electromagnetic stimulation in male professional soccer players did not produce significant improvements in the power and strength of the lower limbs but decreased the peripheral sensitization of the vastus medialis after eccentric exercise protocol.